Implementasi Analisis SWOT dalam Strategi Pemasaran Produk Si Nahdik (Simpanan Amanah Pendidikan) Pada KSPPS BMT Amanah Nusa Wedelan - Muhammad Khoirul latif; Ahmad Fauzan Mubarok (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Purpose- The purpose of this study is to make decisions on the marketing strategy of SIRADIK products at KSPPS BMT Amanah Nusa Wedelan through SWOT analysis. Methods- This research uses a qualitative approach with the SWOT (Strenght, Weakness, Opportunities, Threats) analysis method and combines it with the calculation of IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) weights. This method includes in-depth interviews, observation, and documentation. Results- From the calculation with the IFAS and EFAS approaches, the SI NAHDIK product marketing strategy is in the third coordinate and is included in the classification of turn-around strategies. The steps taken to maximize the product include market segmentation, marketing efficiency, effective use of social media.